The management of bacterial conjunctivitis - Anna Kiełczewska; Aleksandra Kiełczewska; Grzegorz Szcześniak (Journal of Education, Health and Sport)
Introduction and Purpose: Bacterial conjunctivitis, a common eye disease characterized by inflammation of the conjunctiva, poses a major challenge in clinical practice due to its prevalence, diverse etiology and the need for effective pharmacological treatment. The conjunctiva is constantly exposed to the adverse effects of various external and internal factors. This review is devoted to the pharmacological treatment of bacterial conjunctivitis, with a focus on the most common causative agents.